The Analysis of Hedonic Lifestyle Impact on Irrational Purchasing Behavior with Social Acknowledgement as a Moderating Variable - Anggraeni, Yustina; Gunawan, Kartika (Review of Management and Entrepreneurship, 2024)
This study aims to examine the critical role of social acknowledgment in moderating the relationship between hedonic lifestyles and irrational buying behavior, particularly in the context of luxury products among Generation X, Millennials, and Generation Z in Indonesia. The research objective is to assess how social acknowledgment influences the extent to which individuals with hedonic lifestyles engage in irrational purchasing. The method involves purposive sampling, collecting 256 valid responses. The results reveal that while a hedonic lifestyle significantly impacts irrational purchasing decisions, social acknowledgment amplifies this effect, leading individuals to engage in more impulsive and excessive buying behavior. These findings highlight the importance for marketers and corporate policymakers to consider status-oriented and socially acknowledged marketing strategies to effectively target these consumer groups. The implications suggest that social acknowledgment can be a powerful driver in luxury product consumption, emphasizing the need for marketing approaches that resonate with consumers’ desires for social recognition.